Wave-Current Interaction on Offshore Spar Platforms - Tuhaijan, Siti Nor Adha (2011)
Abstract—Various types of offshore structures have been designed since the beginning of oil and gas discovery. They are conventional fixed platform, compliant tower, tension leg platform, spar, and semi-submersible. The oil and gas exploration is now focusing in the deepwater regions as the natural sources from the shallow water regions are facing depletion. In Malaysia, further studies have to be done in order to develop the technology for oil and gas exploration in deepwater. It is well known that the environmental forces are the main sources of lateral loading acting on offshore structures. When the waves propagate towards the large structure, the existence of the currents in the ocean changes the characteristics of the forces acting on it. So, it is important to know the characteristics of the wave-current interaction on the structure. Some possible interaction mechanisms between waves and currents include surface wind stress, bottom friction, wave climate, wave field, depth and current refraction and modulation of the absolute and relative wave period. The two basics methods of dynamic analysis for offshore floating platforms are the frequency domain and time domain analysis. Keywords-Wave-current interaction; Offshore Structure; Frequency Domain Analysis; Time Domain Analysis;